Ethical Criticism of Constitutional Court Decision Number.90/PUU-XXI/2023 Concerning Minimum Age Limits for Presidential and Vice Presidential Candidates - Prasetyo, Yogi; Indiantoro, Alfalachu; Isnandar, Aries (Constitutionale, 2024)
This research article provides a critical analysis of Constitutional Court Decision No. 90/PUU-XXI/2023, focusing on the serious ethical violations committed by judges during the decision-making process. The study is significant due to the impact these violations have had on the legal field. Employing a literature review combined with a legal philosophical approach, the research utilizes relevant literature to investigate the issues surrounding the decision. The findings reveal that the Constitutional Court's ruling was marred by substantial ethical breaches. Additionally, the analysis highlights various weaknesses in the decision, including problematic motives, methods, processes, and the negative consequences arising from the ruling. Overall, the study underscores that the decision, influenced by serious ethical misconduct, is fraught with numerous issues and deficiencies.